Enhancing Control Flow Comprehension Using Zoom Visual Flow (ZViF) Technique To Represent Control Structures - Kadar, Rozita (2011)
When novice users learn programming, they have to comprehend a lot of things related to programming. Many techniques and tools have been developed to help users to improve their program comprehension but most tools are unsuitable for novices. Some tools are not user friendly, some designs are just for expert programmers and some Integrated Development Environment (IDE) are very simple and fail to expose users to the real world environment. These hinder the learning process and may become obstacles to users who have no programming background. The scope of the study is on visualization technique to represent control structures for novice users.